Assessment of the physicochemical properties of the sediment from the Gangetic floodplain wetlands of West Bengal, India, with GIS and a statistical approach - Das, Basanta Kumar; Saha, Ajoy; Das, Archan Kanti; Chandra, Purna; Mondal, Kausik; Kayal, Tania; Chakraborty, Sangeeta; Bhattacharya, Shreya; Sahoo, Bigan Kumar; Jana, Chayna (Frontiers in Environmental Science, 2024)
Introduction Bottom sediments play a pivotal role in wetland productivity, and here, eight Gangetic floodplain wetlands of India were studied to assess the sediment physicochemical characteristics and textural analysis. Methods Sediment samples that were collected from each wetland in monsoon and non-monsoon seasons were analysed. ANOVA, Principal component analysis and multiple correlation analysis were used for statistical analysis. Results and Discussion Throughout the study period, pH (6.90–8.04), EC (0.20–1.64 dS/m), CaCO3 (1.75%–14.50%), available nitrogen (10.22–22.23 mg/100 g sediment), total nitrogen (80.4–333.8 mg/100 g sediment), available phosphorus (0.20–5.61 mg/100 g sediment), and total phosphorus (19.63–173.33 mg/100 g sediment) were recorded. The sediment quality parameters differ significantly (p > 0.05) among the wetlands. Seasonal variation was only observed on total nitrogen and total phosphorus contents. Sediments were dominated by sand. Sediment nutrient (C, N, and P) stoichiometry of wetlands depicted a comparatively little higher C/P (5.96–66.32) ratio and lower C/N (3.34–22.76) and N/P (1.12–9.25) ratios, which revealed that the physicochemical characteristics of the sediments are influenced by anthropogenic sources. Principal component analysis showed the influence of both natural and anthropogenic causes on wetland ecosystems. The geographic information system (GIS) interpolation approach was used in combination with laboratory analysis methods to give a complete spatial resolution of the sediment quality of each wetland. The study suggests that these wetlands’ sediment quality is favorable for fish culture but requires proper management practices to achieve sustainable production. As it is the first time where monitoring physicochemical properties of sediments of these wetlands are presented, this study can be used as a baseline data for comparison in future environmental assessments of the wetlands.